Prawne aspekty wykorzystania technologii cloud computing w sektorze opieki zdrowotnej - Biczysko-Pudełko, Katarzyna (Wydawnictwo C.H. Beck, 2020)
The purpose of the present article is an attempt to answer the question regarding legal implications of using cloud computing technology in the area of healthcare, specifically the possibility to process data regarding health within electronic medical record which is present in such information systems as cloud computing. Therefore, the main background of deliberations are regulations of the European Parliament and the Council of 27 April 2016, on protection of natural persons in regard to processing of personal data and free movement of such data and repealing Directive 95/46/EC (General Data Protection Regulation), and also – on a smaller scale – regulations of Directive of the European Parliament and the Council 2016/1148 of 6 July 2016, regarding resources for a high and common level of security of the Web and information systems within the EU, and regulations of Polish law amended on that basis.
Keywords: cloud computing; personal data; health data; electronic health record; GDPR; Network and Information Systems Directive